The relationship between ethics and literature in light of Levinas’s work - Walczak, Maria (Hybris, 2015)
In my paper I intend to uncover the relationship between ethics and literature. The aforementioned issue is connected to ’ethical turn’ — new orientation in literary studies, which was introduced in the nineties of 20th century. In order to uncover its source of inspiration, I refer to Lévinas’s works, such as Reality and its Shadow, The poet’s vision, Totality and Infinity, Otherwise than Being. I advocate the view that not only Lévinas’s concept of language, but also his account of poetry and responsibility underlie ethical criticism. Therefore, they are regarded as crucial to understand this new approach to literary studies. To illustrate my thesis, I attempt to interpret literary works, i.e. Wordsworth’s and Coetzee’s in light of Lévinas’s concepts.